Population estimate and extractive potential of uçá crab in the post-closed season: subsidies for management in a Conservation Unit of sustainable use (Research, Society and Development, 2020)
Ucides cordatus (Linnaeus, 1763), the uçá crab, is a subsistence resource for the communities surrounding the mangroves of the RDS Municipal Piraquê-açú and Piraquê-mirim (ES, Brazil). In order to subsidize the management of this resource, population and commercial density (extractive potential), the average size of the crabs, the sex ratio, as well as the percentage of open and closed galleries in the post-closed period were estimated in 18 plots of 100m² along the Estuarine System. The population density found was 0.74 ± 0.24 ind./m² and the commercial 0.10 ± 0.05 ind./m², which may indicate continuous exploration of the species in the region. The sex ratio was 2: 3, with carapace width (LC) for males from 55.77 to 80.38 mm and mean of 67.12 ± 6.50 mm, and females from 25.34 to 74.94 mm and a mean of 61.60 ± 11.40 mm, values ​​close to those found in previous studies in the RDS. The similarities regarding the environmental conditions in which the uçá crab populations are found throughout SEPAPM demonstrate the potential for monitoring the species, so management strategies are proposed in order to assist the management of this fishing resource in the Municipal Reserve.